 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
If x 2 +6x+a=0,ax 2 +1x+b=0,have a common root and first equation has equal roots then show that 2a 2 +b=0

```
5 months ago

```							For common roots (6a -1)x +a²-b = 0 x = (b-a²)/(6a -1) Now36 -4a² = 0 a² = 9a = +- 3 Now out this and solve
```
5 months ago
```							Dear studentso the question says there is one common root.now we know for the general equation ax^2+bx+c=0,x = [-b±√(b^2 -4ac)]/2aso assume that x=[-b+√(b^2–4ac)]/2a is the common root.So, for the roots of the given equation (eq.1, x^2+2x+3=0) will bex= [-2±√(2^2–4(1)(3))]/2(1)But we have selected [-b+√(b^2–4ac)]/2a as the common root.so as per the question,x= [-b+√(b^2–4ac)]/2a = [-2+√(2^2–4(1)(3))]/2(1)so now you have the values for a,b, and cHence a=1,b=2,c=3∴a:b:c=1:2:3
```
5 months ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions